Improving Students' Reading Ability in Q.S Al-Ma'un through Listening Team Strategy at SD Negeri 101013 Situnggaling - Pasaribu, Rahmawati (MANDAILING GLOBAL EDUKASIA, 2025)
The main problem in this study is how to improve the reading ability of Q.S al-Ma'un through the listening team strategy in grade V students of SDN No. 101013 Combined with Classroom Action Research (PTK). The limitation of the problem in the discussion discussed is how to improve the reading ability of Q.S al-Ma'un through the listening team strategy at SDN No. 101013 Situnggaling. The purpose of this study is to explain how to improve student learning outcomes in reading Q.S al-Ma'un in the subject of Islamic Religious Education grade V at SDN No. 101013 Situnggaling. In this discussion, the author uses the classroom action research method. PTK is a research activity that seeks to improve the quality of the learning process and outcomes through a cyclical action based on the teacher's in-depth scrutiny of the problems that occur and believes that they will get the best solution for students in their own classroom environment. In the first cycle, students who have not completed or have not reached the KKM are 50% while students who have completed their studies are 50%. The average student learning outcome in the first cycle was 78.33. Based on the results of the test, in this first cycle the success of the research has not been achieved because students have reached the minimum level of completeness set ≤ 80%. In Cycle II, students have achieved 83.33% learning completion. The average student learning outcomes in cycle II have reached 83.5. This shows that Islamic Religious Education using the Listening Team Strategy has been successful because the minimum level of completeness of student acquisition is 80%.